Analysis of the Mourning Period (Ihdad) in The Compilation of Islamic Law Based on Sheikh Arsyad al-Banjari’s View - Zulfikri Zulfikri; Fauziah Lubis (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This study delves into the analysis of the mourning period, known as Ihdad, as stipulated in the Compilation of Islamic Law (KHI) through the lens of Sheikh Arsyad al-Banjari. Ihdad, a mourning period for widows, is acknowledged in the KHI as an obligation, albeit with general articles referring to detailed discussions in fiqh books. The renowned scholar and mufti, Sheikh Arsyad al-Banjari, author of an-Nikah, a comprehensive work on marriage, provides a unique perspective on Ihdad. This research explores Sheikh Arsyad al-Banjari's viewpoint on the mourning period in the KHI, revealing that his conceptualization generally aligns with the KHI. Notably, Sheikh Arsyad al-Banjari outlines prohibited actions for women during Ihdad. However, a distinct feature absent in the Compilation of Islamic Law is the three-day mourning period for women who have lost relatives, a provision emphasized by Sheikh Arsyad al-Banjari. The absence of this provision in the KHI raises questions about its applicability in the future, encouraging further exploration and consideration of Sheikh Arsyad al-Banjari's insights for broader legal implications